A mechatronic system applied to wear particle analysis - Gonçalves, V. D. [UNESP]; Mathias, Mauro Hugo [UNESP] (My University, 2008)
This paper describes the development of a mechatronic system for a predictive maintenance grounded on wear particle analysis. The reckoning of wear particles containing in lubricating industrial oils brings the image acquisition system into being. The ISO 4406:1999 standard is a guide to establish the counting and evaluation processes of particles. The system applied to the acquisition and analysis of the data consists of a digital camera, a monocular microscope and an oil filtering system. A computational program was developed with the application of Visual Microsoft C++ in a way to detain the oil sample image from the microscope slide to the computer screen. Quantitative analyses of the wear debris particles bulk are exploited applying a graphical interface that was developed to render the image processing of the sample test. The implemented system has a reachable cost thus it can be applied for schooling goals and for bolstering laboratories of minor industries and medium size companies.
Keywords: Computational program; Graphical interface; Mechatronic system; Wear particles; Cameras; Computer software; Debris; Image acquisition; Image processing; Mergers and acquisitions; Computer screens; Evaluation processes; Image acquisition systems; ISO 4406; Medium size; Microscope slide; Microsoft (CO); Wear debris; Mechatronics